Power factor control analysis method for power transmission and distribution lines - SHA PENG; MA XUECHAO; TIAN DONGMING; LIU LIANKAI; LI HECHANG; WANG GUOCHUAN; SHEN JUN; WU LIYUN; ZHANG DA; CHENG BAOFANG; YAN FEI; LIU AIJUN (2016)
The invention relates to a power factor control analysis method for power transmission and distribution lines. The power factor control analysis method comprises the steps of collecting telemeasuring data through a power monitoring system, and calculating electric quantity through an electric energy calculation unit; determining a calculation model of power transmission and distribution line loss; performing data processing on the calculation model through an electric energy measuring apparatus to obtain a power factor of an assessment point, wherein the electric energy measuring apparatus performs data processing for one time at certain interval times; and checking the power factor of the assessment point. According to the power factor control analysis method, the power factor of the power transmission and distribution lines can be reasonably calculated and modified according to the structural characteristics of the power transmission and distribution lines; and the power factor of the assessment point can b